The role of iodine in stunting - Fifin Dian Safitri; Siti Haryati (Sarana Ilmu Indonesia (salnesia), 2024)
Stunting is a significant nutritional problem in Indonesia, caused by various factors, including iodine deficiency. Iodine is crucial in child growth and development, especially in brain and nervous system development. This study aims to analyze the relationship between iodine intake and the incidence of stunting in children. The method used is a literature review using indexed sources such as Google Scholar, PubMed, and Google Books, with the keywords